PENGARUH LIKUIDITAS, NET PROFIT MARGIN, DAN PERTUMBUHAN PENJUALAN TERHADAP HARGA SAHAM (STUDI EMPIRIS PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012-2016) - Syafrida anggraini; Syamwil Syamwil (Universitas Negeri Padang, 2018)
The research aims at finding out the effect of likuidity, net profit margin, and sales growth on stock prices. Data analysis is the annual report and financial statements of Property & Real Estate companies listed on Indonesia Stock Exchange in 2012-2016. While the sample was determined by the purposive sampling method to obtain a sample of 28 companies. Type the data used is secondary data obtained from www.idx.co.id. The method of analysis used multiple regression analysis.Based on the results of multiplie regression analysis with the a significance level of 5% the result of the research concluded: (1) Likuidity has effect on stock prices on companies property & real estate listed on the IDX with significace value 0,020 < 0,05. (2) net profit margin has effect on stock prices on companies property & real estate listed on the IDX with significace value 0,000 < 0,05. (3) sales growth has effect on stock prices on companies property & real estate listed on the IDX with significace value 0,005 > 0,05. Keywords: Likuidity, Net Profit Margin, Sales Growth, Stock Prices